Inkrustowane miecze rzymskie z Barbaricum i obszarów przylimesowych Imperium Romanum. Wybrane zagadnienia - Horbacz, Tadeusz J.; Olędzki, Marek (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
Authors discuss the group of swords of Roman origin the blade of which were inlaid with bronze, copper or brass with symbols understood exclusively in the context or religious and cultural changes of Imperium Romanum. The majority of these findings come from Barbaricum (Fig. 1). The set of motifs inlaid on blade is relatively poor and is limited to three groups of symbols (Fig. 6-8). The first one includes figural representations of Roman Gods connected with fighting, victory, purification and reversal of Evil (Mars, Victoria, Minerva). In the second group there are signa militaria in literal meaning (the eagle - the sign of the legion which is accompanied by emblems of smaller organizational units of the legion), the third group consists of images being the symbols of triumph (ornamenta/insignia/triumphalia): laurel wreath and palm of victory. The palmette of Piaski (Fig. 6, 6 b) being the stylized motif of the palm of victory and in such a shape as it is met on shields of Roman legionaries was included among the third group. The stylistics of inlaid works indicates on two lines of plastic solution of the symbol: realistic and schematic convention. In case of figural representation (Mars, Victoria) we face here "static" and "dynamic" canon of the presentation of the figure. The "static" canon is clearly related to realistic convention while the "dynamic" canon to the schematic one.